PJ Masks. Hello Christmas [videorecording (DVD)] (PJ Masks (Television program), 2017)
Join Catboy, Owlette. and Gekko on their nighttime missions, into the night to save the day. Gekko's desire not to take the blame for stealing Cameron's mini-car allows Luna Girl to almost destroy HQ! Owlette tries to get back at Night Ninja by destroying his masterpiece statue, but she learns two wrongs don't make a right.